Strategy for the use of bracket water in rabanet cultivation in a semi-arid region (Research, Society and Development, 2020)
The objective of this study was to evaluate the agronomic performance of radish submitted to brackish water application, in different soils. The work was developed between September and October 2018 in the experimental field of the Department of Technology and Social Sciences of the State University of Bahia, campus III in Juazeiro-BA. The experimental design evaluated was completely randomized, in a factorial scheme, with five water qualities and two soils. The variables analyzed were: total productivity; fresh tuber mass; tuber length; tuber diameter; titratable total acidity; and pH. The use of brackish water supplied the development of radish plants, resulting in productive performance similar to the water supply system. The floss Neossolo provided a greater agronomic performance of the radish plants, when compared to the Oxisol.